Spinal Intramedullary Metastasis of Breast Cancer - Basaran, Recep; Tiryaki, Mehmet; Yavuzer, Dilek; Efendioglu, Mustafa; Balkuv, Ece; Sav, Aydin (HINDAWI LTD, 2014)
Objective. Breast cancer accounts for approximately one-third of all cancers in females. Approximately 8.5 \% of all central nervous system metastases are located in the spinal cord. These patients have rapidly progressing neurological deficits and require immediate examination. The aim of surgery is decompression of neural tissue and histological evaluation of the tumor. In this paper, we present a case of breast cancer metastasis in thoracic spinal intramedullary area which had been partially excised and then given adjuvant radiotherapy. Case. A 43-year-old female patient with breast cancer for 8 years was admitted to our hospital with complaints of weakness in both legs. Eight years ago, she received chemotherapy and radiotherapy. On her neurological examination, she had paraparesis (left lower extremity: 2/5, right lower extremity: 3/5) and urinary incontinence. Spinal MRI revealed a gadolinium enhancing intramedullary lesion. Pathologic examination of the lesion was consistent with breast carcinoma metastasis. The patient has been taken into radiotherapy. Conclusion. Spinal intramedullary metastasis of breast cancer is an extremely rare situation, but it has a high morbidity and mortality rate. Microsurgical resection is necessary for preservation or amelioration of neurological state and also for increased life expectancy and quality.